Total Quality Management Kepala Madrasah Aliyah Darun Najah Karangploso Malang sebagai Upaya Peningkatan Prestasi dan Kedisiplinan Santri di Era Society 5.0 - Ihda Nur Hayati; Erny Fitroh Nabila Muwafiqi (Jurnal Pengabdian Masyarakat, 2025)
Madrasah management is a matter of considerable concern because it will have an impact on national development. The purpose of this research is to reveal the total quality management (TQM) planning carried out by the Head of Madrasah Aliyah Darun Najah Karangploso Malang, as well as the implementation and evaluation of TQM results applied by the Head of Madrasahs to related educational institutions. As for the results of the study, it can be concluded that the TQM planning of the Madrasah MA Darun Najah Karangploso Malang Principal in improving the discipline and achievement of students in the era of society 5.0 is by using 3 basic principles of TQM, namely continuous improvement, the kaizen system and cultural change. Meanwhile, in the implementation of TQM, the Madrasah Principal made several effective breakthroughs to achieve expectations, namely: (1) digital attendance (2) all-in-one applications that can be accessed by all madrasah residents (3) application of blended learning-based learning to all subjects and (4) provision of intracurriculars that are tailored to the talents, interests and passion of students. Those it can be obtained from the TQM Evaluation of the Head of MA Darun Najah Karangploso Malang that it leads to the improvement and improvement of the quality of students, both discipline and achievement.